Pemberian Metode Progressive Muscle Relaxation Exercise Terhadap Kadar Hemoglobin (Hb) pada Remaja Putri - Amarseto, Binuko; Ariyanti, Lilik; Awanis, Almas (Jurnal Farmasi (Journal of Pharmacy), 2019)
Teenage age is a transition from childhood to adulthood. In adolescence many changes occur, namely physical changes due to increased muscle mass, increased fat tissue in the body, hormonal changes also occur. Adolescent girls are one of the groups who are prone to suffering from iron nutritional anemia due to menstruation or periodic periods that release iron every month. One technique for relaxation is PMR Jacobson's technique. PMR according to Jacobson is a skill that is learned and used to reduce or eliminate tension and cause a sense of comfort without depending on the subject outside himself. PMR is used to reduce anxiety, stress, or tension.This study aims to determine the effect of the provision of progressive muscle relaxation exercise methods on hemoglobin (Hb) levels in young women. This research is a pre-experimental study using a one group pretest-posstest design. Data collection was carried out using a questionnaire. The research sample is adolescents, amounting to 90 people using simple random sampling technique. Data analysis using the Wilcoxon test with a significance level of 5%.The results of the study found that the highest number of respondents was the 10 study groups with 32 respondents (35.6%) while the number of respondents in the 11 study groups was 30 respondents (33.3%) and the most 12 study groups consisted of 28 respondents (31.1%) . showed that there was an effect of the administration of progressive muscle relaxation exercise methods to hemoglobin (Hb) levels in adolescent girls (p <0.05). From the results of this study it can be concluded that progressive muscle relaxation exercise can increase the influence of hemoglobin (Hb) levels in adolescent girls. Physical activity can affect hemoglobin levels because the nutrients consumed enter the body are assisted by the process for the formation of hemoglobin (Hb).